Taxonomy of the Hirtodrosophila melanderi species group (Diptera: Drosophilidae), with descriptions of four new species from southwestern China - Katoh, Takehiro K.; Zhang, Guang; Zhou, Chuan-Jiang; Gao, Jian-Jun (Zootaxa, 2018)
The Hirtodrosophila melanderi species group contains nine known species recorded from either the Old or the New World. All these species were thought to be strict fungivorous drosophilids. In the present study, we give supplementary descriptions for three of these known species, all recorded from Yunnan, southwestern China, H. furcapenis, H. furcapenisoides, and H. longifurcapenis, by examining respective type specimen(s). We then describe four new species of the same group, H. seticlasper Katoh & Gao, sp. nov., H. spinicerca Katoh & Gao, sp. nov., H. serratifurcapenis Katoh & Gao, sp. nov., and H. truncifurca Katoh & Gao, sp. nov., all discovered recently from high altitudes (ca. 3,500 to 3,800 m a.s.l.) in Tibet (Xizang), southwestern China. The delimitation of these new species is firstly performed in light of morphology and further with the aid of DNA sequences of the mitochondrial COI (cytochrome c oxydase, subunits I) gene. In addition, a key to all the species of the species group is provided.